Is it necessary to perform occupational audiometric testing at 6-months of employment? - Silva,Vagner Antonio Rodrigues da (2022)
Abstract Introduction: Current Brazilian legislation requires that all workers exposed to noise are to be given an audiogram upon hiring, after 6 months of employment (first periodic test), and annually after the first periodic test. In other countries, the regulations of hearing conservation programs do not include the requirement for audiometric testing at 6 months of employment, but only annually. There is no evidence that the periodicity adopted by Brazilian legislation is the most appropriate. Objective: The present study aimed to evaluate the first 3 occupational audiometric tests of workers exposed to noise. Methods: Historical cohort study with cross-sectional analysis. Participants were all male metallurgy workers aged up to 40 years. The first 3 audiograms of each worker were analyzed: pre-employment audiometric test, periodic audiometric test 1, and periodic audiometric test 2. For each worker, mean frequency thresholds were calculated at 3, 4, and 6 kHz in the left and right ears for each test. Statistical analysis was performed using the nonparametric Wilcoxon test. Results: A total of 988 workers were included. There was a significant difference in auditory thresholds between the pre-employment test and the 2 subsequent periodic tests for the right and left ears. There was no significant difference between Test1 and Test2 in either ear. Conclusion: Given the lack of difference between the first 2 periodic tests, we believe that they could be merged into a single test, i.e., first periodic audiometric testing could be performed at 12 months of employment without compromising workers’ health.